Soluble recombinant enterovirus 71 VP1 fused to truncated newcastle disease virus nucleoprotein elicits immune responses in mice - Mustafa, Suhaili; Abd-Aziz, Noraini; Yusoff, Khatijah; Shafee, Norazizah (Springer Nature, 2025)
Introduction: Enterovirus 71 (EV71) is a major causative agent of hand, foot, and mouth disease with potential neurological complications, highlighting the urgent need for effective vaccines. The viral protein 1 (VP1) contains major antigenic and neutralizing epitopes, making it a promising target for subunit vaccine development. Aims: This study evaluated the immunogenicity of a recombinant VP1 fragment (amino acids 198-297) fused to a truncated Newcastle Disease Virus nucleoprotein (NPt-VP1t). Materials and methodology: Soluble NPt-VP1t (SP) and insoluble NPt-VP1t (IB) versions of the protein were expressed in E. coli, purified, and verified by SDS-PAGE and Western blot using anti-VP1 and anti-NDV antibodies, confirming the ~59 kDa fusion protein. Adult female BALB/c mice were immunized intraperitoneally with SP, IB, or PBS control, with two booster doses at two-week intervals. Results: Results demonstrated that mice immunized with the SP formulation produced significantly higher anti-VP1 IgG reactivity than those receiving the IB or controls (p < 0.05). After the first booster (week 4), the antibody level in the SP was approximately 2-fold higher than the IB, with the highest OD readings observed at week 8 post-immunization. The SP maintained high antibody levels for at least two weeks post-booster. Splenocyte proliferation assays revealed that the SB group had a stimulation index (S.I.) of 0.826 ± 0.104, about 1.6 times greater than the IB group (p < 0.05). Cytokine profiling showed significantly elevated Th1 (IFN-γ, IL-2) and Th2 (IL-4, IL-6, IL-10) cytokines in both SP and IB groups compared to controls (p < 0.05), with IFN-γ levels markedly higher in vaccinated mice, indicating activation of both humoral and cell-mediated immunity. SDS-PAGE of the IB protein revealed contaminant bands, suggesting the actual amount of NPt-VP1t administered was lower than in the soluble formulation, potentially affecting its immunogenicity. All groups received formulations with Freund’s adjuvant, which may limit assessment of vaccine-specific safety. Conclusion: Overall, the SP recombinant NPt-VP1t protein elicited robust humoral and cellular immune responses in mice, outperforming the insoluble form. These findings support the immunogenic potential of SP as a subunit vaccine candidate for EV71. Future studies should include viral challenge and neutralization assays to confirm protective efficacy.